2020
DOI: 10.1039/c9dt03291f
|View full text |Cite
|
Sign up to set email alerts
|

Dicerium letterbox-shaped tetraphenolates: f-block complexes designed for two-electron chemistry

Abstract: Well-defined dinuclear lanthanide complexes: stabilisation of both CeIII and CeIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Recently, tetraphenolate ( p TP = [{2‐(OC 6 H 2 R 2 ‐2,4) 2 CH}‐C 6 H 4 ‐1,4] 4− ) ligands were used to access the metallacyclic 2+2 [Ce IV 2 ( p TP R ) 2 (THF) 4 ] ( 35 ) (R = Me, t Bu) with an unusual “letterbox” topology. This was achieved via the oxidation of the Ce III analogue [K(THF) n ][Ce 2 ( p TP R ) 2 (THF) 4 K] ( 36 ) with a range of oxidants (CuX 2 [X = Cl, OTF), I 2 , XeF 2 , HgX 2 (X = Cl, I, OAc)], involving a rare concerted two‐electron redox process within a single molecule [90] . Solution electrochemistry (THF with 0.1 m [ n Bu 4 N][PF 6 ]) indicates significant stabilization of the Ce IV cation (−1.83 V vs. Fc/Fc + ).…”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 99%
“…Recently, tetraphenolate ( p TP = [{2‐(OC 6 H 2 R 2 ‐2,4) 2 CH}‐C 6 H 4 ‐1,4] 4− ) ligands were used to access the metallacyclic 2+2 [Ce IV 2 ( p TP R ) 2 (THF) 4 ] ( 35 ) (R = Me, t Bu) with an unusual “letterbox” topology. This was achieved via the oxidation of the Ce III analogue [K(THF) n ][Ce 2 ( p TP R ) 2 (THF) 4 K] ( 36 ) with a range of oxidants (CuX 2 [X = Cl, OTF), I 2 , XeF 2 , HgX 2 (X = Cl, I, OAc)], involving a rare concerted two‐electron redox process within a single molecule [90] . Solution electrochemistry (THF with 0.1 m [ n Bu 4 N][PF 6 ]) indicates significant stabilization of the Ce IV cation (−1.83 V vs. Fc/Fc + ).…”
Section: Lanthanoid Complexes With Unusual Lanthanoid Oxidation Statesmentioning
confidence: 99%
“…The syn conformation is drawn for simplicity for each cerium complex in Scheme 1, although both conformers have been observed by us in X-ray diffraction studies of related metal complexes. 46,47,52 X-ray structural analyses of some of the bimetallic group 1, 5, and 13 complexes of the phenols H 4 (pTP t ) and H 4 (mTP t ) also confirm the rotational freedom of the central arene bridge, although to our knowledge, no solution-state studies of their behavior have been reported. 46,49,50,53 1 H− 1 H NOESY NMR spectroscopic experiments were conducted to investigate the ambient solution-state conformation for the siloxide and aryloxide complexes.…”
Section: ■ Introductionmentioning
confidence: 66%
“…Only a few solid state structures exist of TP complexes in the syn conformation, in the letterbox-shaped di-U IV complex [U 2 (mTP) 2 ], the M-M distance is 6.57 Å, 52 and in the open di-Ce III complex [Ce 2 (BH 4 ) 2 (pTP t )], the M-M distance is 10.85 Å. 47 For example, there is a maximum separation in the anti-conformation of 9.32 Å in [U 2 I 4 (mTP t )(THF) 4 ] and 10.40 Å in [U 2 I 4 (pTP t )(THF) 4 ]. 46,67 To further test the effect of metal-metal distance on catalytic activity, we have also made the new terphenyl bridged complex 4 in which the Ce-Ce distance is far too large for cooperativity.…”
Section: Ring-opening Copolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, high‐energy‐resolution fluorescence detection X‐ray absorption spectroscopy (HERFD‐XAS) has been used to analyse a formal di‐cerium(IV) phenolate complex and confirmed mixed valency with considerable 4f 0 character [138] . In addition, the multiconfigurational ground state of formal Ce IV complexes stabilised by imidophosphorane ligands or imidophosphorane‐functionalised guanidinate ligands has been established through Ce L 3 ‐edge XANES studies [139–141] .…”
Section: Spectroscopic Singularitiesmentioning
confidence: 99%